Determinar la composición de los tejidos del pasto llanero (Andropogon gayanus) con fertilización química y orgánica en diferentes estados de madurez en la época lluviosa. - Martínez Gavilánez, Darwin Leonel (2024)
Pastures and forages are part of the diet of cattle. They provide ruminants with minerals such as Nitrogen, Phosphorus, Potassium, Calcium, Iron, among others, which are vital for a cattle diet. For this reason, to achieve all the appropriate levels, these grasses need fertilization programs, whether chemical or organic. The objective of the research was to determine the composition of the tissues of plain grass with chemical and organic fertilization in different stages of maturity in the rainy season. The research was carried out at Sacha Wiwa research center which is located at 500 m above sea level, in the pasture and forage garden. For statistical analysis, a completely randomized block design was used with a Tukey test at 5% probability. The research had three treatments with seven repetitions and three experimental units. The mentioned treatments were: chemical fertilization (Urea + DAP + Muriate of potassium) and organic fertilization which consisted of the application of Biol. The treatment that influenced the most for the development of the grass was chemical fertilization, so obtaining a total forage production of 1414.29 g., plant height 183.43 cm, stem weight 1022.52 g. and leaf weight 343.82 g. after 75 days. According to tissue analysis, the concentrations were captured in different stages of maturity, however, they were obtained with chemical fertilization. To conclude, the best treatment was obtained with the application of chemical fertilization (Urea + DAP + Muriate of potassium).